Exploring functional literacy in Junior High School - Setyawan Pujiono; Jamilah Jamilah (Universitas Ahmad Dahlan, 2021)
Literacy competence becomes a fundamental need for students to support their learning process at school. Likewise, the contribution of functional literacy is very important in living a social life and communicating in the current 4.0 era effectively. This article aimed to describe the form of functional literacy and the obstacles in the implementation of functional literacy program in junior high schools in Yogyakarta. This article used library research and direct observation of the implementation of functional literacy in schools as the research method. The results of the study showed that, first, functional literacy program implemented in schools was still merely accustomed to reading and writing. Schools, in general, have made literacy programs such as reading posts, library visits, work exhibitions, meaningful writing, writing as a response, writing exhibitions, and creative and academic writing. However, the implementation of functional literacy towards the development, learning, and functional needs of students has not been planned and implemented optimally. Second, the constraints on the implementation of functional literacy came from the students and the schools. In addition to the students' lack of motivation, feeling unfocused, tired, and bored also hindered the effectivity of literacy program implementation. The constraints stemming from schools included the lack of budget for literacy programs, the lack of time allocation and new reference sources, and no collaboration between school members in the implementation of literacy programs. The literacy programs were implemented using top-down approach, and have not yet referred to the basic functional needs of students.